Basics and alternatives concerning the measurement of company performances - IONESCU, Cicilia (Journal of Economic Development, Environment and People, 2016)
In a competitive economy, a company's activity aims to achieve strategic objectives. Of these, two objectives: making profit and meeting the needs of a particular market segment are vital targets to maintaining the company’s market position. This requires information which reveals the company's financial position and profitability. The companies which want to be competitive must assess the company's capacity to generate positive results and cash in a reliable way. This strategy needs information on the resources used and the results obtained, but should not overlook the truth that the profit arises from uncertainty and the risk assumed by the entrepreneur. In this regard, the International Accounting Standards often use the term "probability" when referring to the recognition criteria of structures comprised in the financial statements.